(untitled) (Global Journal of Medical Research, 2024)
The aim of this study was to evaluate the degree of knowledge of dentists from the state of Alagoas regarding the preventive means of periodontal diseases. The crosssectional observational study was carried out using an online questionnaire with 14 questions related to the preventive means of periodontal disease. 154 questionnaires were collected and answered by dentists registered on regional dental council of Alagoas. The sample was chosen by convenience without distinction of specialization and gender. 154 professionals were evaluated, 100% of the interviewees answered that knew some means of preventing periodontal disease and the most prevalent method known by the professionals was Oral Hygiene Instruction 98.7% and the dental floss 98%. Regarding the knowledge of these professionals about the types of brushing techniques, 95% affirmed know the techniques and 5% did not.